Microencapsulation of Juniper and Black Pepper Essential Oil Using the Coacervation Method and Its Properties after Freeze-Drying - Alicja Napiórkowska; Arkadiusz Szpicer; Iwona Wojtasik-Kalinowska; Maria Dolores Torres Perez; Herminia Dominguez González; Marcin Andrzej Kurek (Foods, 2023)
Essential oils are mixtures of chemical compounds that are very susceptible to the effects of the external environment. Hence, more attention has been drawn to their preservation methods. The aim of the study was to test the possibility of using the classical model of complex coacervation for the microencapsulation of essential oils. Black pepper (Piper nigrum) and juniper (Juniperus communis) essential oils were dissolved in grape seed (GSO) and soybean (SBO) oil to minimize their loss during the process, and formed the core material. Various mixing ratios of polymers (gelatin (G), gum Arabic (GA)) were tested: 1:1; 1:2, and 2:1. The oil content was 10%, and the essential oil content was 1%. The prepared coacervates were lyophilized and then screened to obtain a powder. The following analyses were determined: encapsulation efficiency (EE), Carr index (CI), Hausner ratio (HR), solubility, hygroscopicity, moisture content, and particle size. The highest encapsulation efficiency achieved was within the range of 64.09–59.89%. The mixing ratio G/GA = 2:1 allowed us to obtain powders that were characterized by the lowest solubility (6.55–11.20%). The smallest particle sizes, which did not exceed 6 μm, characterized the powders obtained by mixing G/GA = 1:1. All powder samples were characterized by high cohesiveness and thus poor or very poor flow (CI = 30.58–50.27, HR = 1.45–2.01).